(untitled) (Research, Society and Development, 2025)
The aim of this article is to present a case study of the rapid diagnosis of scalded skin syndrome in order to establish appropriate treatment and reduce the risk of complications arising from the syndrome. Scalded skin syndrome is an infection predominantly caused by Staphylococcus aureus, resulting from the hematogenous dissemination of exotoxins to the skin, causing detachment of the granulosa zone of the epidermis. Therefore, its destruction and exfoliation of the skin in a localized or generalized way. It is important to emphasize that the infectious focus is far from the release of the exotoxin through inflammation. It mainly affects children under five years of age, but can occur in adolescents and adults with an underlying disease. In this case, this is a male patient, 1 year old, black, presenting with spots on the skin associated with fever, which progressed to hyperemia and blisters on the trunk, upper limbs and face. With a pathological history of pharyngitis in the week before the clinical presentation, amoxicillin was administered. After medical evaluation, he was diagnosed and began intravenous treatment with Ceftriaxone and Oxalicin, in addition to dermatological care. After 10 days of hospital treatment, he was discharged and progressed without scars.